Pengaruh Gradasi Agregat Terhadapkecepatan rembesan dan kekedapan air pada beton dengaqn agregat asal sungai krasak - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Watertight concrete is required for water-retaining structures and waterworks, such as roofs, basement walls, water towers, bridge piers, irrigation structures, etc. Indonesian National Standard for the watertight concrete has been made. The standard has stated the specifications of the method of .making the watertight concrete, such as the grading of the fine aggregate and the coarse agggregate, but it has not stated what is the proporsion of the aggregates nor the grading !Unit of the all in aggregate, and so the specifications of the aggregate properties. Experiment had been done to obtain the effects of the grading of aggregates and the using of aggregate from Krasak River to the waterproofing of the concrete. Four types of grading of all in aggregates were used for designing of concrete mixes. The concrete mixes were designed with 380 kg of cement per meter cubic of concrete and water cement ratio of The concrete cubes that were made with these mixes were tested to obtain the permeability and the water absorption of the concrete. The result indicated that the greater of the coarse aggregate grading is more permeable the concrete and that the aggregate from Krasak River will be able to be used for making watertight concrete for normal water if the concrete mix is designed with the Indonesian National Standard for the watertigth concrete.